Sugarcane bagasse derived nano magnetic adsorbent composite (SCB-NMAC) for removal of Cu2+ from aqueous solution - Wannahari, R. (Asian Research Publishing Network, 2018)
A novel sugarcane bagasse derived nano magnetic adsorbent composite (SCB-NMAC) was successfully prepared for the removal of Cu2+ in aqueous solution. Characterization of the newly prepared material was obtained through SEM, EDX, particle size analyzer and XRD. Results confirmed the presence of iron oxide coating onto the material. The removal of Cu2+ by SCB-NMAC obeyed the pseudo second order reaction (R2 = 0.982) as opposed to intra particle diffusion (R2 = 0.708), and pseudo first order (R2= 0.402) model. Langmuir isotherm was found to be more applicable (R2= 0.996) rather than Freundlich isotherm (R2= 0.979), which indicated a monolayer adsorption between Cu2+ and SCB-NMAC. The maximum adsorption capacity was calculated as 113.63 mg/g at pH 4. In addition, adsorption-desorption studies indicated that SCB-NMAC displayed high stability for regeneration with good reusability with desorption efficiency up to 60 and reusability efficiency up to 80 for three recurring cycles. Â© 2006-2018 Asian Research Publishing Network (ARPN).